2004
DOI: 10.3184/003685004783238481
|View full text |Cite
|
Sign up to set email alerts
|

Helicobacter Pylori: Current Status and Future Prospects

Abstract: Helicobacter pylori is a global pathogen that causes severe gastrointestinal diseases leading to a significant morbidity and mortality. There is an effective treatment for peptic ulcer disease, however, this is being compromised by an increase in the prevalence of antibiotic resistance. Although alternative rescue regimens have been advocated, the best strategy would be to prevent disease, especially in the case of gastric cancer for which there is still no treatment. One approach is to inhibit the first step … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 88 publications
0
4
0
Order By: Relevance
“…The idea of a bacterial etiology for human cancer is by no means limited to the oral cavity. Indeed, it is readily apparent that H. pylori infection is causally associated with malignancies of gastric epithelia ( 111 , 112 ), leading to the categorization of this organism as a WHO class I carcinogen. H. pylori causes inflammation of the gastric mucosa, likely by inducing gastric epithelial cells to secrete IL-8, which results in recruitment of inflammatory cells to the site of infection ( 113 ).…”
Section: The Contribution Of the Oral Microbiomementioning
confidence: 99%
“…The idea of a bacterial etiology for human cancer is by no means limited to the oral cavity. Indeed, it is readily apparent that H. pylori infection is causally associated with malignancies of gastric epithelia ( 111 , 112 ), leading to the categorization of this organism as a WHO class I carcinogen. H. pylori causes inflammation of the gastric mucosa, likely by inducing gastric epithelial cells to secrete IL-8, which results in recruitment of inflammatory cells to the site of infection ( 113 ).…”
Section: The Contribution Of the Oral Microbiomementioning
confidence: 99%
“…It is well known that Helicobacter pylori is associated with chronic atrophic gastritis and the development of gastric cancer [26,27]. It has been reported that ectopic expression of activation-induced cytidine deaminase (AID), a gene-editing enzyme, in gastric mucosal epithelium due to infection with H. pylori which harbors a gene family called 'cag' pathogenicity island (cagPAI) might be a mechanism of mutational accumulation in gastric carcinogenesis [28].…”
Section: Involvement Of Oral Bacteria In the Development And Progression Of Oral Cancermentioning
confidence: 99%
“…Helicobacter pylori is the best known bacterium causally linked with cancer leading its categorization as a WHO class I carcinogen (84)(85)(86)(87). According to IARC Working Group on the Evaluation of Carcinogenic Risks to Humans, 1994 majority of cancers induced by Helicobacter pylori infections is related to the inflammation caused by bacterium (87,88), Infections may alter the tumor microenvironment by inducing the expression of cytokines involved in cell proliferation, and migration.…”
Section: 1-role Of Periodontal Microflora In Carcinogenesis 311-micro...mentioning
confidence: 99%